Training 1st-Year Medical Undergraduates in Doctor–Patient Relationships Using Gagne’s Model of Instructional Design - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Archives of Medicine and Health Sciences)
The doctor–patient relationship is an extremely important and indispensable aspect of health-care delivery. Instructional design refers to a structured strategy that a teacher adopts to develop and deliver any educational program or a specific topic in a streamlined manner. Gagne’s model of instructional design has been employed to deliver a wide range of skills in different settings. The topic of the doctor–patient relationship can be explained to the 1st-year undergraduate medical students as a part of the attitude, ethics, and communication module training. The proposed time for the session is 1 h, and we intend to employ a wide range of teaching–learning methods (namely flipped classroom; interactive discussion using case vignettes; employment of movies depicting a doctor–patient relationship; and role play, use of pear deck) to promote interaction and active engagement, and reflective writing. To summarize, the doctor–patient relationship is an integral part of health-care delivery and we must train students in this regard. Gagne’s model of instructional design provides both teachers and students an opportunity to learn the knowledge in a comprehensive and student-centered manner.